2017
DOI: 10.1002/jsfa.8416
|View full text |Cite
|
Sign up to set email alerts
|

Models to improve the non‐destructive analysis of persimmon fruit properties by VIS/NIR spectrometry

Abstract: The proposed strategy, for outlier removal and wavelength reduction, allowed the achievement of useful results. Principal component regression fit/prediction capability produced excellent results. Conversely, partial least squares regression showed fair/poor results and the remaining tested models performed badly on real data. © 2017 Society of Chemical Industry.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(21 citation statements)
references
References 50 publications
0
21
0
Order By: Relevance
“…The calibration model accuracy was described by the coefficient of determination for the calibration data set (R 2 c ) and validation data set (R 2 p ), root mean square error of cross-validation (RMSECV), and root mean square error of prediction (RMSEP). In addition, the ratio of prediction to deviation value (RPD) was calculated [9,22] by dividing the standard deviation (SD) to the RMSECV or the RMSEP. RPD results below 1.5 indicated that the calibration was not useful.…”
Section: Chemometric Analysismentioning
confidence: 99%
“…The calibration model accuracy was described by the coefficient of determination for the calibration data set (R 2 c ) and validation data set (R 2 p ), root mean square error of cross-validation (RMSECV), and root mean square error of prediction (RMSEP). In addition, the ratio of prediction to deviation value (RPD) was calculated [9,22] by dividing the standard deviation (SD) to the RMSECV or the RMSEP. RPD results below 1.5 indicated that the calibration was not useful.…”
Section: Chemometric Analysismentioning
confidence: 99%
“…Statistical multilinear correlation, built using spectra in the visible range (VIS) (380–740 nm) and / or in the near‐infrared range (NIR) (700–2500 nm), allows the quick prediction of some important properties of agricultural foodstuffs, as has been demonstrated for milk, cereals, vegetables and fruits, during fruit processing operations, and also when monitoring fungicide content in water during the dipping treatment of citrus fruit . The results of the NIR analysis confirm the possibility of measure oil and water content in the olive paste and pomace …”
Section: Introductionmentioning
confidence: 60%
“…The forecasting capability must be statistically quantified using techniques such as cross‐validation (CV), involving the random partitioning of samples into complementary subsets such as k‐fold CV, or leave‐one‐out CV. These methods allow the prediction capability of the model to be estimated, measured by the widespread ratio of standard deviation of calibration data to standard error of prediction data (RPD), as described extensively in the literature . An RPD ≥5.0 indicates that the model can be used in quality control.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…So far, NIR technology has been successfully applied to detect the internal quality of fruits with thin peel, such as pears, peaches, apples, kiwifruits and persimmons, and so on (Altieri, Genovese, Tauriello, & Direnzo, 2017;Bobelyn et al, 2010;Clark et al, 2004;Fan, Zhang, Li, Huang, & Wang, 2016;Nascimento et al, 2016;Nicolaï, Verlinden, Desmet, & Torricelli, 2008). However, compared with this type of fruit, it may be more difficult to assess the internal quality of fruits with thick peel such as melons and watermelons by NIR spectroscopy (Ito et al, 2002), because effective collection of the spectral information is more difficult for fruits with thick peel.…”
Section: Introductionmentioning
confidence: 99%